2001
DOI: 10.1589/jpts.13.1
|View full text |Cite
|
Sign up to set email alerts
|

What Measure of Lower Extremity Muscle Strength Best Explains Walking Independence?

Abstract: This study was conducted to determine if any one strength measure or combination of strength measures provided an explanation of ambulatory independence among 107 acute rehabilitation patients. This was a retrospective, descriptive, and correlational study where ambulatory function was quantified using the Functional Independence Measure (FIM). Lower extremity strength was quantified by sit to stand performance, and knee extension force measured by manual muscle testing and hand held dynamometry. Descriptive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In addition, walking speed had a very significant correlation with the lower and upper limb muscle strength, endurance, and levels of alertness. Functional fitness, the ability to perform normal everyday activities independently and safely, is one of the most important issues for older people 21) . As discussed above, the degradation of cognitive functions may cause problems in ADL and instrumental activities of daily living (IADL) that require adequate lower limb muscle strength, endurance and alertness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, walking speed had a very significant correlation with the lower and upper limb muscle strength, endurance, and levels of alertness. Functional fitness, the ability to perform normal everyday activities independently and safely, is one of the most important issues for older people 21) . As discussed above, the degradation of cognitive functions may cause problems in ADL and instrumental activities of daily living (IADL) that require adequate lower limb muscle strength, endurance and alertness.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the physical performance of elderly individuals decreases with age [1][2][3][4] . The present study demonstrated that gait ability, balance function and lower extremity force decline with age.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activities including gait ability and balance function decrease with age [1][2][3][4] . These decreases increase the risk of falls in daily living and make it difficult for elderly individuals to live a self-supporting life.…”
Section: Introductionmentioning
confidence: 99%
“…Post operative function is determined by regaining the optimal strength in this muscle and many rehabilitation programmes include strengthening of gluteus medius. The strength of this muscle provides lateral stability to the trunk and pelvis and is essential during one legged stance and also during the stance phase of gait [12]. However there is a paucity of evidence in the literature examining specific changes in this muscle despite anecdotal evidence that reduced strength in this muscle is responsible for gait impairment and reduced balance [13].…”
Section: Introductionmentioning
confidence: 99%